KAJIAN KEBIJAKAN VAKSINASI TERHADAP ANGKA PENURUNAN CORONA VIRUS 19 BERBASIS BIG DATA TABLEAU ANALISIS DI INDONESIA 2023: STUDY OF VACCINATION POLICY ON REDUCING RATE OF CORONA VIRUS 19 BASED ON BIG DATA TABLEAU ANALYSIS IN INDONESIA 2023 - Mustikaningsih, Wening (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study analyzes Minister of Health Regulation Number 10 of 2021, which focuses on COVID-19 vaccination implementation in Indonesia. The research combines qualitative and quantitative data using Big Data Analysis techniques such as data mining and text mining. The study reveals that the graph comparison of fully vaccinated individuals in Indonesia demonstrates a reduction in new cases of the COVID-19 variant, indicating a high level of public participation in the vaccination policy. These findings highlight the effectiveness of the vaccination program in combating the COVID-19 pandemic in Indonesia